Analisis Penggunaan Mistar Hitung Braille Dalam Menyelesaikan Operasi Hitung Bilangan Bulat bagi Penyadang Tunanetra Di SLB Negeri Kanatang - Elsy Senides Hana Taunu; Darius Imanuel Wadu; Yuliana Tamu Ina Nuhamara; Rambu Maya Imung Maharani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the use of braille slide rules for blind people in improving numeracy skills, especially in operating integers. The type of research used in this study is a descriptive analysis method. The approach used in this study is a qualitative approach. Data collection techniques used in this study are Tests, Observations, and Interviews. The sample in this study amounted to 3 people with a population of 3 people at SLB Negeri Kanatang. The sampling technique in this study used a sampling technique. Blind children. The results of the study show that the use of braille slide rules is very good for blind children because the use of braille slide rules can make it easier for students to perform integer arithmetic operations. This study emphasizes the importance of providing appropriate teaching aids to support the inclusion and independence of blind children in the learning process.